The effect of vitamin 25-(OH)-D3 on Glucocorticoid Receptor-β (GRβ) and 25-(OH)-D receptors in idiopathic nephrotic syndrome patients - Krisni Subandiyah; Harinda Khanifa Khusna (Pediatric Sciences Journal, 2020)
Backgound: Idiopathic Nephrotic Syndrome (INS) is the most chronic glomerular disease in children. Glucocorticoid is the main therapy acts by binding to glucocorticoid receptor α (GRα), whereas it is reported that glucocorticoid receptor β (GRβ) is a main inhibitor of GRα. The interaction between glucocorticoid receptors and vitamin D can increase anti-inflammation at glucocorticoid receptors, thereby decreasing GRβ levels. This study was aimed to investigate the effect ssupplementation of vitamin D3 on GRβ and 25-(OH)-D level in children with INS and the correlation between both of parameters. Method: A randomized clinical trial, double blind, pre and post-test control group was conducted among 30 subjects with newly diagnosed as INS. Subjects were divided into 2 groups, group 1 (G1) were treated with prednisone and vitamin D3 whereas group 2 (G2) were only treated with prednisone. The level of GRβ and 25-(OH)-D level was measured by ELISA method. Data were analyzed using SPSS version 17 for Windows. Result: There was significant elevation of 25-(OH)-D plasma between G1 (31.46 ± 9.69 ng/mL) and G2 (13.43±17.25 ng/mL) (p<0.001), and significant decrease of GRβ levels between G1 (-13.71 ± 8.06 ng/mL) and G2 (-0.917 ± 3.76 ng/mL) (p<0.000). Pearson testing first group showed that vitamin D level was positively correlated with GRβ levels (r=0.458; p= 0.01). Conclusion: The effect supplementation of vitamin D3 can increase 25-(OH)-D level and decrease of GRβ levels significantly in children with idiopathic nephrotic syndrome who receive glucocorticoid therapy.